Operability analysis of SWATH as a service vessel for offshore wind turbine in the southeastern coast of China. (1st May 2022) - Li, Binbin; Qiao, Dongsheng; Zhao, Wenhua; Hu, Zhenzhong; Li, Sunwei
Abstract: The operability of service operation vessels (SOV) is highly concerned with the cost, schedule, and weather window to the operation and maintenance of offshore wind farms. SWATH (Small Waterplane Area Twin Hull) vessel is introduced as a novel application as SOV to be deployed off the coast of southeastern China, an investigation into the operability for walk-to-work (W2W) on-site service using the new type of vessel is conducted in this study. The features of SWATH's motion behavior are discussed by performing a seakeeping analysis, which is compared to a similar size monohull SOV. W2W operation and various operational limits associated with vessel and gangway dynamic response are modeled by the numerical method established in the frequency domain. Considering different W2W transfer approaches and wave headings, an in-depth analysis regarding the limiting wave height is carried out, the operability of three sites off the southeastern coast of China is predicted. SWATH demonstrates the excellent operability for both transversal and longitudinal transfer approaches as well as the robustness against arbitrary wave heading. The fuel consumption under the high sea-state shows higher usage compared to the monohull by a qualitative estimation using the second-order mean drift forces. With the average operability greater than 95% in the study, SWATH has proven to be an attractive type of vessel against monohull whose operability may drop to 60% to 80% in case of unfavorable heading or transfer approach. Due to lack of damping, the optimization of SWATH geometry and proper damping device may help further improve the operability by suppressing resonant heave and roll. Highlights: SWATH (Small Waterplane Area Twin Hull) was studied as a novel service operation vessel for offshore wind farms. An in-depth analysis of Walk-to-work operation regarding various configurations was conducted. Operability for three sites off the southeastern coast of China was predicted for SWATH and a monohull. Fuel consumption was qualitatively assessed, optimization towards maximum operability was discussed.